Metode Penelitian Analisis Semiotik Media Sosial - Pranindita Dwi Fadhila; Chintya Almira; Aldi Priatmana (STIT Sirojul Falah Bogor, 2022)
Semiotics or semiotics are terms that refer to the same science. Semiotics is commonly used by American scholars, although the term semiotics is more commonly used in Europe. Semiotics comes from the Greek word semeion, which means 'sign', or the English sign, which means 'signal'. Semiotics is known as a science that studies sign language systems such as languages, codes, signals, and human language. Semiotics is the science of symbols. To be able to read and interpret these symbols, we need